Impulsively Generated Linear and Non-Linear Alfvén Waves in the Coronal Funnels - Chmielewski, P.; Srivastava, A.K.; Murawski, K.; and et. al. (Polska Akademia Nauk, 2013)
We present simulation results of the impulsively generated linear and non-linear Alfvén waves in the weakly curved coronal magnetic ffux-tubes (coronal funnels) and discuss their implications for the coronal heating and solar wind acceleration. We solve numerically the time-dependent magnetohydrodynamic equations to find the temporal signatures of the small and large-amplitude Alfvén waves in the model atmosphere of open and expanding magnetic field configuration with a realistic temperature distribution. We compute the maximum transversal velocity of both linear and non-linear Alfvén waves at dierent heights of the model atmosphere, and study their response in the solar corona during the time of their propagation. We infer that the pulse-driven non-linear Alfvén waves may carry sufficient wave energy ffuxes to heat the coronal funnels and also to power the solar wind that originates in these funnels. Our study of linear Alfvén waves shows that they can contribute only to the plasma dynamics and heating of the funnel-like magnetic ffux-tubes associated with the polar coronal holes.
Keywords: Impulsively generated linear and non-linear alfvén waves; Coronal Funnels; Magnetohydrodynamics; Plasma diagnostics